Perjanjian Kawin Dalam Perkara Sengketa Waris (Analisis Terhadap Putusan Nomor 21/Pdt.G/2022/PN Plk) - Novea Elysa Wardhani; Sudiarti, Elin; Claudia Yuni Pramitha (UNES Law Review, 2024)
Marriage is a form of permanent relationship, which is carried out by a man and a woman, recognized as legitimate by the community concerned based on the applicable marriage regulations. Before entering into a marriage, the prospective husband and prospective wife can make a marriage agreement, which regulates the assets obtained before marriage, as well as the assets obtained after marriage. The assets obtained after marriage are related to the inheritance rights given to the heirs in the marriage. Indeed, the marriage agreement made must not conflict with the applicable positive law. If the marriage agreement is made not in accordance with the provisions of positive law, then the marriage agreement has no legal force if in the future there is a dispute between the parties related to the marriage.